Fatwa MUI Jawa Timur Tentang Etika Dakwah Di Era Digital: Analisis Maqshid Al-Syari’ah - Abd Shamat; Ahmad Norma Pemata (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The The issuance of the Indonesian Ulema Council (MUI) East Java Fatwa No. 06 of 2022 on the ethics of preaching in the digital age is based on the phenomenon of preaching in the digital age, which has undergone significant shifts. This has attracted the interest of researchers to explore further the correlation between this fatwa and Maqāṣid al-Sharī‘ah, whether the fatwa constitutes a restriction on religious expression. In this context, the Maqāṣid al-Sharī‘ah approach developed by Jasser Auda serves as the primary analytical tool to assess to what extent the fatwa reflects the objectives of Islamic law. The results of the study show that this fatwa represents Maqāṣid values such as Protection of Freedom of Belief (al-Huriyyah al-I’tiqod), Protection of Human Rights (Hifdz al-huquq al-Insan), Preservation of Reason (Hifz al-Aql), Honor (ḥifẓ al-‘ird), Family (ḥifẓ al-usrah), and Property (ḥifẓ al-māl). By emphasizing ethics, tolerance, and caution in delivering da'wah in the digital space, this fatwa not only safeguards the integrity of Islamic da'wah but also plays a role in building an inclusive, harmonious society that aligns with the fundamental values of Islam. Fatwa MUI, Preaching Ethics, Maqasid Al-Shari‘Ah, Jasser Auda.